The association of antihypertensive agents with MRI white matter findings and with Modified Mini-Mental State Examination in older adults. - Heckbert, S R; Longstreth, W T; Psaty, B M; Murros, K E; Smith, N L; Newman, A B; Williamson, J D; Bernick, C; Furberg, C D (J Am Geriatr Soc, 1997)
OBJECTIVES: To examine the association of antihypertensive regimen with magnetic resonance imaging (MRI) white matter hyperintensity and with cognitive impairment in older adults. DESIGN: Cross-sectional study. SETTING: The Cardiovascular Health study, an observational prospective cohort study of risk factors for coronary heart disease and stroke in men and women 65 years of age and older. PARTICIPANTS: 1268 men and women with pharmacologically treated hypertension. MEASUREMENTS: Information on medication use, medical history, and health habits was collected at clinic examinations. Participants completed the Modified Mini-Mental State Examination (3MS) and underwent MRI examination. Without clinical information, study neuroradiologists assigned an overall grade of white matter signal intensity on MRI on a scale from 0 (no findings) to 9 (extensive findings). RESULTS: Adjusted mean white matter grade was higher for users of calcium channel blockers (2.59, P = .007) and users of loop diuretics (2.60, P = .015) than for users of beta blockers (2.12). The association was present for both dihydropyridine and non-dihydropyridine calcium channel blockers. Adjusted mean 3MS scores were lower for users of calcium channel blockers (89.6, P < .002), especially dihydropyridines, and users of loop diuretics (89.7, P < .006) than for users of beta blockers (92.3). No statistically significant association could be shown for users of other drug regimens, including thiazides and ACE inhibitors. CONCLUSION: In this study, users of antihypertensive regimens which included calcium channel blockers or loop diuretics had more severe white matter hyperintensity on MRI and worse performance on 3MS than users of beta blockers.
Keywords: Adrenergic beta-Antagonists; Aged; Aged, 80 and over; Antihypertensive Agents; Brain; Calcium Channel Blockers; Cognition; Cohort Studies; Cross-Sectional Studies; Diuretics; Female; Geriatric Assessment; Humans; Magnetic Resonance Imaging; Male; Risk Factors

High body fatness, but not low fat-free mass, predicts disability in older men and women: the Cardiovascular Health Study. - Visser, M; Langlois, J; Guralnik, J M; Cauley, J A; Kronmal, R A; Robbins, J; Williamson, J D; Harris, T B (Am J Clin Nutr, 1998)
Using data from the Cardiovascular Health Study, we studied the relation between body composition (fat mass and fat-free mass, assessed by bioelectrical impedance) and self-reported, mobility-related disability (difficulty walking or stair climbing) in 2714 women and 2095 men aged 65-100 y. In a cross-sectional analysis at baseline (1989-1990), disability was reported by 26.5% of the women and 16.9% of the men. A positive association was observed between fat mass and disability. The odds ratio for disability in the highest quintile of fat mass was 3.04 (95% CI: 2.18, 4.25) for women and 2.77 (95% CI: 1.82, 4.23) for men compared with those in the lowest quintile. Low fat-free mass was not associated with a higher prevalence of disability. In a longitudinal analysis among persons not reporting disability at baseline, 20.3% of the women and 14.8% of the men reported disability 3 y later. Fat mass at baseline was predictive of disability 3 y later, with odds ratios of 2.83 (95% CI: 1.80, 4.46) for women and 1.72 (95% CI: 1.03, 2.85) for men in the highest quintile of fat. The increased risk was not explained by age, physical activity, chronic disease, or other potential confounders. Low fat-free mass was not predictive of disability. The results showed that high body fatness is an independent predictor of mobility-related disability in older men and women. These findings suggest that high body fatness in old age should be avoided to decrease the risk of disability.
Keywords: Adipose Tissue; Aged; Aged, 80 and over; Body Composition; Cross-Sectional Studies; Disability Evaluation; Female; Geriatric Assessment; Health Surveys; Humans; Male; Obesity; Predictive Value of Tests; Walking

Predicting future years of healthy life for older adults. - Diehr, P; Patrick, D L; Bild, D E; Burke, G L; Williamson, J D (J Clin Epidemiol, 1998)
Cost-effectiveness studies often need to compare the cost of a program to the lifetime benefits of the program, but estimates of lifetime benefits are not routinely available, especially for older adults. We used data from two large longitudinal studies of older adults (ages 65-100) to estimate transition probabilities from one health state to another, and used those probabilities to estimate the mean additional years of healthy life that an older adult of specified age, sex, and health status would experience. We found, for example, that 65-year-old women in excellent health can expect 16.8 years of healthy life in the future, compared to only 8.5 years for women in poor health. We also provide estimates of discounted years of healthy life and future life expectancy. These estimates may be used to extend the effective length of the study period in cost-effectiveness studies, to examine the impact of chronic diseases or risk factors on years of healthy life, or to investigate the relationship of years of life to years of healthy life. Several applications are described.
Keywords: Aged; Aged, 80 and over; Cost-Benefit Analysis; Female; Forecasting; Health Promotion; Health Status; Humans; Life Expectancy; Life Tables; Male; Probability; Quality-Adjusted Life Years; Sex Factors